Disclosure of HIV status to children in resource‐limited settings: a systematic review. Issue 1 (27th May 2013) - Vreeman, Rachel C; Gramelspacher, Anna Maria; Gisore, Peter O; Scanlon, Michael L; Nyandiko, Winstone M
Abstract : Introduction: Informing children of their own HIV status is an important aspect of long‐term disease management, yet there is little evidence of how and when this type of disclosure takes place in resource‐limited settings and its impact. Methods: MEDLINE, EMBASE and Cochrane Databases were searched for the terms hiv AND disclos* AND (child* OR adolesc*). We reviewed 934 article citations and the references of relevant articles to find articles describing disclosure to children and adolescents in resource‐limited settings. Data were extracted regarding prevalence of disclosure, factors influencing disclosure, process of disclosure and impact of disclosure on children and caregivers. Results: Thirty‐two articles met the inclusion criteria, with 16 reporting prevalence of disclosure. Of these 16 studies, proportions of disclosed children ranged from 0 to 69.2%. Important factors influencing disclosure included the child's age and perceived ability to understand the meaning of HIV infection and factors related to caregivers, such as education level, openness about their own HIV status and beliefs about children's capacities. Common barriers to disclosure were fear that the child would disclose HIV status to others, fear of stigma and concerns for children's emotional or physical health. Disclosure was mostly led by caregivers and conceptualized as a one‐time event, while others described it as a gradual process. Few studies measured the impact of disclosure on children. Findings suggested adherence to antiretroviral therapy (ART) improved post‐disclosure but the emotional and psychological effects of disclosure were variable. Conclusions: Most studies show that a minority of HIV‐infected children in resource‐limited settings know his/her HIV status. While caregivers identify many factors that influence disclosure, studies suggest both positive and negative effects for children. More research is needed to implement age‐ and culture‐appropriate disclosure in resource‐limited settings.